(untitled) (Research, Society and Development, 2021)
The relentless pursuit of competitive advantage in the industrial sector contributes to the realization of the importance of controlling primary production resources. This research is based on the high index of idleness generated by the lack of essential resources for the manufacture of the product, linked to the lack of management of these. The objective of this study is to identify and analyze the production stoppage rates due to lack of raw material, to propose improvements that ensure clear process fluidity and productivity gains for operators, in addition to helping managers in decision making. It is characterized as a case study through direct observation and bibliographic research, in addition to having a mixed approach (quali-quantitative) evidenced by the description of an explanatory research. Data collected in the company were explored to build the solidity of the article, through the numbers of production stops, finished products affected by the lack of material and main items and their respective frequency of absenteeism in the stock. In this way, it was possible to build the ABC curve of finished products and raw materials, allowing the visualization of materials that demand greater attention and care to always keep active in the warehouse, as they are the ones that most rotate in the warehouse. Finally, through the analysis of the information, it is concluded that it is necessary to restructure the material list of the finished products so that it is possible to run the MRP, in addition to the adoption of a routine of rotating inventories based on the ABC Curve of inputs to generate accuracy indexes and ensure control of processes.